Enhancing Professionalism In Young Accountants Through Al-Islam And Kemuhammadiyahan Values In Accounting Education - Bonnix Hedy Maulanaa; Muhammad Abdul Rozaq; Toni Ardi Rafsanjani (Politeknik Siber Cerdika Internasional, 2024)
This study aims to explore the values of Al Islam and Kemuhammadiyahan (AIK) which will be a differentiator for accounting graduates and be able to provide added value for their graduates for industrial needs. The added value is that accountants are professional and ethical. The research was conducted with a descriptive qualitative approach. This research involves in-depth interviews with third-year (final) students and analysis of accounting learning documents. The data was analyzed using thematic analysis techniques to uncover emerging patterns and themes. The results of the study show that AIK values that need to be integrated in accounting learning such as honesty, responsibility, simplicity, ethics and integrity are the main values. In the end, AIK's values will be in line with realizing competent and ethical accountants. Another finding is that the obstacles in the implementation of AIK are the lack of knowledge and academic rules that have not been fully supported and the lack of support from professional organizations. This study also revealed that students realize that AIK values can convince them to be competent when becoming accountants in various industries. This research makes theoretical and practical contributions in understanding the role of religious values in the religious-based education model in order to produce graduates who are competent and uphold high ethics.